How urban densification shapes walking behaviours in older community dwellers: a cross-sectional analysis of potential pathways of influence - Cerin, Ester; Barnett, Anthony; Zhang, Casper J. P.; Lai, Poh-chin; Sit, Cindy H. P.; Lee, Ruby S. Y. (International journal of health geographics, 2020)
Population growth, population ageing, and urbanisation are major global demographic trends that call for an examination of the impact of urban densification on older adults' health-enhancing behaviours, such as walking. No studies have examined the pathways through which urban densification may affect older adults' walking. This information is key to evidence-based, health-oriented urban and transport planning. This study aimed to identify neighbourhood environment characteristics potentially responsible for the effects of neighbourhood densification on older adults' frequency and amount of transportation and recreation walking within and outside the neighbourhood. The Active Lifestyle and the Environment in Chinese Seniors (ALECS) project collected self-reported data from 909 older adults (≥ 65 years) living in 128 physically and socially diverse neighbourhoods in Hong Kong (71% response rate). Walking was measured using the Neighbourhood Walking Questionnaire for Chinese Seniors. Objective residential density and other neighbourhood environmental attributes were assessed using Geographic Information Systems. Generalised additive mixed models examined the total effects of neighbourhood residential density on walking and the mediating role of other environmental attributes and car ownership. A complex network of potential pathways of positive and negative influences of neighbourhood residential density on different aspects of walking was revealed. While residential density was positively related to within-neighbourhood transportation and outside-neighbourhood recreation walking only, it exhibited positive and/or negative nonlinear indirect effects on all examined aspects of walking via recreation, public transport, food/retail and street intersection densities, and/or car ownership. High-density environments appear to support within-neighbourhood walking by providing access to food and retail outlets via well-connected street networks and discouraging car ownership. However, extreme density may lead to reductions in walking. Public transport density accompanying high-density areas may facilitate outside-neighbourhood walking but deter within-neighbourhood walking. The development of activity-friendly communities for ageing populations need to consider these opposing influences.